2015
DOI: 10.5414/cp202152
|View full text |Cite
|
Sign up to set email alerts
|

The genetic polymorphisms of POR*28 and CYP3A5*3 significantly influence the pharmacokinetics of tacrolimus in Chinese renal transplant recipients

Abstract: The study demonstrated that the POR*28 C>T mutation could decrease the C0/D of tacrolimus in renal recipients who were CYP3A5 expressers. The population pharmacokinetic model showed that the combined genotype of CYP3A5-POR was associated with the CL/F of tacrolimus which might provide references for personalized use of tacrolimus in clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 0 publications
2
24
0
2
Order By: Relevance
“…Contrasting with these observations, a number of previous studies have failed to highlight the benefit of introducing CYP3A4 ∗ 22 in modeling Tac inter-individual variability through popPK-approaches, with a few exceptions (Shi et al, 2011; Zuo et al, 2013; Zhang et al, 2015; Moes et al, 2016; Andreu et al, 2017). This is not surprising as the majority of studies were performed in Asian populations where CYP3A4 ∗ 22 is absent, as it is for individuals of African origins.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Contrasting with these observations, a number of previous studies have failed to highlight the benefit of introducing CYP3A4 ∗ 22 in modeling Tac inter-individual variability through popPK-approaches, with a few exceptions (Shi et al, 2011; Zuo et al, 2013; Zhang et al, 2015; Moes et al, 2016; Andreu et al, 2017). This is not surprising as the majority of studies were performed in Asian populations where CYP3A4 ∗ 22 is absent, as it is for individuals of African origins.…”
Section: Discussionmentioning
confidence: 94%
“…However, even if the amplitude of the CYP3A4 ∗ 22 effect might be comparable to that of CYP3A5 ∗ 3 , the CYP3A4 ∗ 22 influence is not as statistically significant probably because of the wide PK variability observed among the CYP3A4 ∗ 22 carriers. As a consequence, it may also explain why it is not always identified as a significant covariate when considering the few studies reported to date (Shi et al, 2011; Zuo et al, 2013; Zhang et al, 2015; Moes et al, 2016). Another possible explanation is the fact that CYP3A5 ∗ 3 completely blunts the CYP3A5 activity whereas for CYP3A4 ∗ 22 , some isoenzyme activity remains.…”
Section: Discussionmentioning
confidence: 99%
“…46 In another study of 24 adult Native American kidney transplant recipients, CYP3A5*3 had a higher AF (0.94). 7 CYP3A5*3 is the most-studied CYP3A5 variant in association with tacrolimus and has been evaluated in Europeans, 18,21,[47][48][49][50][51][52] African Americans, 5,24,35,53 Asians, 52,[54][55][56][57][58][59][60] and Native Americans. Allele Frequency…”
Section: Discussionmentioning
confidence: 99%
“…However, the goal of this study was not to identify all the factors related to variability but to study if variability in trough concentration and dose adversely affects transplant outcomes. Lastly, our study did not consider rarer genetic variants, such as CYP3A4*22 or POR*28, which have been shown to influence TAC metabolism to a lesser extent …”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors are also well‐known to account for TAC pharmacokinetics differences between patients and several single‐nucleotide polymorphisms (SNPs) have been associated with TAC troughs, including CYP3A5*3, CYP3A5*6, CYP3A5*7, CYP3A4*22, and possibly POR*28 . CYP3A5*3, *6, and *7 variants are loss‐of‐function alleles and significantly reduce the metabolic clearance of TAC .…”
Section: Introductionmentioning
confidence: 99%